Insights about exosomal circular RNAs as novel biomarkers and therapeutic targets for hepatocellular carcinoma - Haiyan Zhang; Haiyan Zhang; Shanshan Pei; Jiaxuan Li; Jiajie Zhu; Hongyu Li; Guangshang Wu; Ruiqi Weng; Ruyi Chen; Zhongbiao Fang; Jingbo Sun; Keda Chen (Frontiers Media S.A., 2024)
One of the most prevalent pathological types of Primary Liver Cancer (PLC) is the Hepatocellular Carcinoma (HCC) poses a global health issue. The high recurrence and metastasis rate of HCC, coupled with a low 5-year survival rate, result in a bleak prognosis. Exosomes, small extracellular vesicles released by various cells, contain diverse non-coding RNA molecules, including circular RNAs (circRNAs), which play a significant role in intercellular communication and can impact HCC progression. Studies have revealed the potential clinical applications of exosomal circRNAs as biomarkers and therapeutic targets for HCC. These circRNAs can be transferred via exosomes to nearby non-cancerous cells, thereby regulating HCC progression and influencing malignant phenotypes, such as cell proliferation, invasion, metastasis, and drug resistance. This review provides a comprehensive overview of the identified exosomal circRNAs, highlighting their potential as non-invasive biomarkers for HCC, and suggesting new perspectives for HCC diagnosis and treatment. The circRNA from exosomal organelles promotes metastasis and immune scape because of their unique chirality which is different from the Biomolecular Homochirality.